2018
DOI: 10.2147/ott.s184078
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG5 promotes growth and invasion in melanoma by regulating the miR-26a-5p/TRPC3 pathway

Abstract: IntroductionMelanoma has been reported as the most common malignancy in skin cancer. The small nucleolar RNA host gene 5 (SNHG5), an lncRNA, has been proven as a vital regulator in several types of carcinoma. This study was designed to investigate the detailed roles and possible mechanisms of SNHG5 in melanoma progression.MethodsQuantitative real-time PCR (qRT-PCR) analysis was conducted to detect the expression levels of SNHG5, miR-26a-5p and transient receptor potential, canonical 3 (TRPC3) mRNA in melanoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…Accumulating research has confirmed the importance of lncRNAs in tumorigenesis. 17,18 In HCC, several lncRNAs were identified as important regulators. For instance, SNHG16 overexpression suppresses HCC cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating research has confirmed the importance of lncRNAs in tumorigenesis. 17,18 In HCC, several lncRNAs were identified as important regulators. For instance, SNHG16 overexpression suppresses HCC cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Through miR-26 sponging and up-regulation of TRPC3 (transient receptor potential channel 3), SNHG5 stimulates melanoma cell growth. The exogenous knockdown of SNHG5 in melanoma cells in vitro decreases their proliferation rate and invasive capacity, while it stimulated apoptosis (91). Further research and details on the role of SNHG5 in malignant diseases are presented in Supplementary Table 3.…”
Section: Small Nucleolar Rna Host Gene 5 (Snhg5)mentioning
confidence: 99%
“…2 Due to melanoma's susceptibility to metastasis, the prognosis of melanoma patients with advanced disease is unfavorable, with five-year survival rates below 20%. 3 Therefore, clarifying the mechanisms of melanoma pathogenesis and establishing biomarkers for early diagnosis and therapy would be a significant milestone in improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%